1968
DOI: 10.1136/thx.23.6.652
|View full text |Cite
|
Sign up to set email alerts
|

The use of tracheostomy following major open cardiac surgery: a review of 64 cases

Abstract: in patients unfdergoing major open-heart surgery are reviewed. The indications and complications are classified, and the high incidence of secondary infection is discussed briefly. Tracheal stenosis or dilatation occurred in six patients (9 4%) and the contributory factors are discussed in greater detail.Tracheostomy is one of the oldest established procedures in surgical practice, but the indications for its use have undergone considerable changes, particularly in the last 25 years (Borman and Davidson, 1963)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
2

Year Published

1971
1971
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…This is certainly an important cause of damage to the trachea (Gray, 1960;Jackson, 1963 ;Watts, 1963;Stiles, 1965a;Gibson, 1967;Johnston et al, 1967;Nicholls, 1968;Shelly et al, 1969;Jewsbury, 1969;James et al, 1970). It has been suggested that the length of the tracheal damage caused by the cuff may depend upon movement of the tracheostomy tube relative to the trachea, movement increasing the length of the damage (James et al, 1970).…”
Section: Movement Of Tracheostomy Tube In Tracheamentioning
confidence: 99%
See 4 more Smart Citations
“…This is certainly an important cause of damage to the trachea (Gray, 1960;Jackson, 1963 ;Watts, 1963;Stiles, 1965a;Gibson, 1967;Johnston et al, 1967;Nicholls, 1968;Shelly et al, 1969;Jewsbury, 1969;James et al, 1970). It has been suggested that the length of the tracheal damage caused by the cuff may depend upon movement of the tracheostomy tube relative to the trachea, movement increasing the length of the damage (James et al, 1970).…”
Section: Movement Of Tracheostomy Tube In Tracheamentioning
confidence: 99%
“…Gibson (1967) considered that trauma from the cuff and infection were the two main factors responsible for destruction of the full thickness of a segment of the tracheal wall leading either to malacia or stenosis. Johnston et al (1967) thought that infection was one of the three major factors responsible for stenosis (the other two being pressure and movement), a view reiterated by Nicholls (1968). Putney (1955) and Meade (1961) believed it was important to leave the tracheostomy wound open lest abscess formation occur with spread of infection along facial planes to the mediastinum, leading to the production of tracheal stenosis.…”
Section: Movement Of Tracheostomy Tube In Tracheamentioning
confidence: 99%
See 3 more Smart Citations